Cryptography Tutorials - Herong's Tutorial Examples - Version 5.36, by Dr. Herong Yang
Blowfish Decryption Algorithm
This section describes the Blowfish decryption algorithm, which is identical to the encryption algorithm step by step in the same order, only with the sub-keys applied in the reverse order.
The decryption algorithm of a block cipher should be identical to encryption algorithm step by step in reverse order. But for Blowfish cipher, the encryption algorithm is so well designed, that the decryption algorithm is identical to the encryption algorithm step by step in the same order, only with the sub-keys applied in the reverse order.
To help us to approve the decryption algorithm, we have to write the encryption algorithm and the decryption algorithm with temporary variables.
Encryption algorithm with temporary variables:
Input: T: 64 bits of clear text P1, P2, ..., P18: 18 sub-keys F(): Round function Output: C: 64 bits of cipher text Algorithm: (L0, R0) = T, dividing T into two 32-bit parts L1 = L0 XOR P1 R2 = R0 XOR F(L1) XOR P2 L3 = L1 XOR F(R2) XOR P3 R4 = R2 XOR F(L3) XOR P4 L5 = L3 XOR F(R4) XOR P5 R6 = R4 XOR F(L5) XOR P6 L7 = L5 XOR F(R6) XOR P7 R8 = R6 XOR F(L7) XOR P8 L9 = L7 XOR F(R8) XOR P9 R10 = R8 XOR F(L9) XOR P10 L11 = L9 XOR F(R10) XOR P11 R12 = R10 XOR F(L11) XOR P12 L13 = L11 XOR F(R12) XOR P13 R14 = R12 XOR F(L13) XOR P14 L15 = L13 XOR F(R14) XOR P15 R16 = R14 XOR F(L15) XOR P16 L17 = L15 XOR F(R16) XOR P17 R18 = R16 XOR P18 C = (R18, L17)
Decryption algorithm with temporary variables:
Input: CC: 64 bits of cipher text P1, P2, ..., P18: 18 sub-keys F(): Round function Output: TT: 64 bits of clear text Algorithm: (LL0, RR0) = CC, dividing CC into two 32-bit parts LL1 = LL0 XOR P18 RR2 = RR0 XOR F(LL1) XOR P17 LL3 = LL1 XOR F(RR2) XOR P16 RR4 = RR2 XOR F(LL3) XOR P15 LL5 = LL3 XOR F(RR4) XOR P14 RR6 = RR4 XOR F(LL5) XOR P13 LL7 = LL5 XOR F(RR6) XOR P12 RR8 = RR6 XOR F(LL7) XOR P11 LL9 = LL7 XOR F(RR8) XOR P10 RR10 = RR8 XOR F(LL9) XOR P9 LL11 = LL9 XOR F(RR10) XOR P8 RR12 = RR10 XOR F(LL11) XOR P7 LL13 = LL11 XOR F(RR12) XOR P6 RR14 = RR12 XOR F(LL13) XOR P5 LL15 = LL13 XOR F(RR14) XOR P4 RR16 = RR14 XOR F(LL15) XOR P3 LL17 = LL15 XOR F(RR16) XOR P2 RR18 = R16 XOR P1 TT = (RR18, LL17)
Here is how to approve the decryption algorithm:
Let: T: 64 bits of clear text C: 64 bits of cipher text encrypted from T CC: 64 bits of cipher text TT: 64 bits of clear text decrypted from CC If: CC = C Then: TT = T Prove: (LL0, RR0) = CC Initializing step in decryption = C Assumption of CC = C = (R18, L17) Finalizing step in encryption LL1 = LL0 XOR P18 Applying P18 in decryption = R18 XOR P18 Previous result = R16 XOR P18 XOR P18 Applying P18 in encryption = R16 RR2 = RR0 XOR F(LL1) XOR P17 Applying P17 in decryption = L17 XOR F(R16) XOR P17 Previous result = L15 XOR F(R16) XOR P17 XOR F(R16) XOR P17 Applying P17 in encryption = L15 ...... LL17 = LL15 XOR F(RR16) XOR P2 Applying P2 in decryption = R2 XOR F(L1) XOR P2 Previous result = R0 XOR F(L1) XOR P2 XOR F(L1) XOR P2 Applying P2 in encryption = R0 RR18 = RR16 XOR P1 Applying P1 in decryption = L1 XOR P1 Previous result = L0 XOR P1 XOR P1 Applying P1 in encryption = L0 TT = (RR18, LL17) Finalizing step in decryption = (L0, R0) Initializing step in encryption = T
Last update: 2015.
Table of Contents